Meat semi-finished products for a healthy lifestyle - Chernyushok, Olga; Shevchenko, Ivanna; Biryuk, Yulia (My University, 2020)
The problem in the market of semi-finished products, due to the lack of protein sand mineral sin the body, has been studied. The effect of freezing on the storage of semi-finished products is brie fly described. It is proposed to enrich by adding to the recipe of whey enriched with Mg and Mn. The useful substances contained in milk proteins, which are proposed to be included in the recipe of meat products, are listed. The influence of these components on the organoleptic characteristics of the product is described. Досліджено проблему на ринку напівфабрикатів, у зв’язку з нестачею білків та мінеральних речовин в організмі. Коротко описано вплив заморожування на зберігання напівфабрикатів. Запропоновано збагатити, за допомогою внесення до рецептури молочної сироватки збагаченої Mg та Mn. Наведено корисні речовини, які містяться у молочних білках, які запропоновано внести в рецептуру м’ясного напівфабрикату. Описано вплив даних компонентів на органолептичні показники продукту.
Keywords: milkwhey; magnesium; semi-finished products; meat; dumplings; recipe; молочна сироватка; магній; напівфабрикати; м'ясо; пельмені; рецептура; кафедра технології м’яса і м’ясних продуктів